A low cycle fatigue life model for a shot peened gas turbine disc alloy. (July 2019) - Eriksson, Robert; Moverare, Johan; Chen, Zhe
Highlights: Shot peening gave fatigue life benefit for low loads. Benefit from shoot peening vanishes for high loads. Residual stresses are removed in the first cycle, but influence the mean stress. Benefit from residual stress was captured with a mean stress theory. Abstract: Turbine disks in gas turbines are subjected to cyclic load at high temperature, making, especially the fir tree type blade attachments, susceptible to fatigue. Shot peening of the fir tree attachments may be used to increase the fatigue life by introducing compressive residual stresses. In the current study, both polished and shot peened notched specimens made from alloy 718 were subjected to low cycle fatigue at 450–550 °C. The shot peening generally increased the fatigue life, although the effect diminished for high loads. It was shown that the effect of shot peening could be handled as mean stress effects in a life model based on a Smith–Watson–Topper (SWT) type parameter, σ max Δ ε / 2 . A material model which captured the mean stress was set up to get the SWT parameter at the notch root. It was shown that thermal relaxation of residual stresses and initial strain hardening from cold work could be excluded from the finite element analysis used to establish the mean stress; this since the plasticity in the first cycle dominated the plastic deformation of the specimen. Overall, the SWT-based life model worked satisfactorily. However, the prediction of correct mean stresses at 550 °C proved somewhat difficult as the degree of mean stress relaxation at this temperature varies widely in available literature data.